EXPLORAREA BIBLIOTECII CA SPAŢIU INFOCULTURAL: REALITĂŢI ŞI PERSPECTIVE - UNGUREANU, şef oficiu, Biblioteca Centrală, Diana; ROGALNICOV, bibliotecar, Biblioteca Centrală, Cristina; editor (BIBLIOPOLIS, 2020)
This communication deals with the guidelines that were took by the bibliomedia in the relation of the public with the library, in the light of realities and perspectives, connecting them to the specific case of the Central Library. There was noted a succesion of advantages, disadvantages, remarkable successes and in- adequacies to which we must work and/or are working yet. In addition to traditional activities, therewereanalyzedinnovations, i.e. forms of activity involving innovative elements, such as reading campaigns, flashmobs, creative di- versity in the design of the halls for activities, promoting library services and resources, in- teractive cast and post-event stage, emphasis being placed on the description of the mode of interaction of the youth with the library. Later, there was continued with the demonstration of greater benefit of the Central Library – part- nerships, by addressing the full range of activi- ties that were conducted in partnership with the library of Lavena and Italian Embassy in Chişinău, and by presenting the most impor- tant collaborations of international order, the result of which was the opening in the Central Library of the English Book Hall.